Perception Of The Role Of Farmers in Extension Rural Agribusiness Development ( Puap ) in The Lembah Damai Village Rumbai Pesisir District Pekanbaru City - Ridwan Sani; Roza Zulida; Arifudin ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimed to determine: (1) farmers' perceptions of the role of agricultural extension in rural agribusiness development (PUAP), (2) perception PUAP development; 57 respondents from Gapoktan Manunggal Jaya been interviewed, which is taken by proportionate random sampling. The results showed that: (1) farmers perceive extension function well in mentoring PUAP this can be seen from a score of 2.53 with the category of done, which consists of a role as an educator; education, the dissemination of information / innovation, as a companion, as a consultant, as coaching, as observers, and evaluation, (2) according to farmers PUAP program in the period 2008- 2011 have a good development. It can be seen from the scores by category done 2.87. Output indicator shows the prevalence PUAP funds received by farmers to undertake farming while outcome indicators show that the existence of the program PUAP farmers really feel the change in earnings, and also lead to greater success PUAP agribusiness activities in rural areas. Keywords : PUAP Program‟s, Farmers Perception , Role Extension